Memetized Learning: How Humor-Infused Stories Can Engage Geography Students in the Digital Age - Kudzayi Savious Tarisayi (Indonesian Journal of Educational Research and Technology, 2024)
Scholars have long recognized the power of traditional storytelling for engaging students and enhancing the learning experience. This study explores how integrating memes into storytelling, creating "memetized stories", can be an innovative strategy to teach geography concepts. Utilizing constructivism as a theoretical lens, in-depth interviews were conducted with 10 geography teachers who integrate memetized stories into their teaching. The findings reveal that memetized stories can be utilized in student projects, presentations, and to teach environmental issues, cultural sensitivity, and critical thinking skills. Integrating memetized stories into these pedagogical activities promotes active student participation, collaborative learning, and increased engagement and interest in the subject matter. However, teachers must ensure that memetized stories are used appropriately and sensitively. When done well, memetized stories provide a visual and humorous means for students to learn geography concepts through interaction with visual media, aligning with multimodal learning approaches. This study provides valuable insights into the potential benefits and drawbacks of incorporating memetized stories into the geography curriculum. Overall, the findings suggest that memetized stories can be an innovative and engaging strategy for teaching geography to millennial students in the digital age.